1989
DOI: 10.1136/bmj.298.6685.1421
|View full text |Cite
|
Sign up to set email alerts
|

Antenatal ultrasonography to detect fetal renal abnormalities: a prospective screening programme.

Abstract: Objective-To evaluate screening for abnormalities of the fetal renal tract by ultrasonography and to determine the incidence of such abnormalities in a population.Design-A 12 month prospective population study. Foliow up of infants to between 9 and 18 months.Setting-A district general hospital. Participants-6292 Pregnant women reaching 28 weeks' gestation within the study period.Interventions-Antenatal ultrasound scanning was offered to all of the women. Babies in whom an abnormality of the renal tract had bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
1
7

Year Published

1992
1992
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 195 publications
(24 citation statements)
references
References 10 publications
0
16
1
7
Order By: Relevance
“…The prevalence of congenital anomalies of the kidney and the urinary tract as detected during the antenatal period has been reported as being between 0.1% and 0.7%. [ 3 4 5 ] There is a major paucity of literature related to the prevalence of antenatally diagnosed kidney and urinary tract anomalies in Saudi Arabia. The high rate of consanguinity marriages in Saudi Arabia[ 6 ] compared to the developed countries necessitates recognition of the prevalence and pattern of these anomalies in order to take the appropriate steps in prevention and management, thereby reducing end-stage renal disease in Saudi society.…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of congenital anomalies of the kidney and the urinary tract as detected during the antenatal period has been reported as being between 0.1% and 0.7%. [ 3 4 5 ] There is a major paucity of literature related to the prevalence of antenatally diagnosed kidney and urinary tract anomalies in Saudi Arabia. The high rate of consanguinity marriages in Saudi Arabia[ 6 ] compared to the developed countries necessitates recognition of the prevalence and pattern of these anomalies in order to take the appropriate steps in prevention and management, thereby reducing end-stage renal disease in Saudi society.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies confirm that the severity of hydronephrosis correlates positively with postnatal hydronephrosis, need for surgery and risk of UTI, and negatively with spontaneous resolution. [5723252728] While fetuses with minimal pelvic dilatation (5-9 mm) have low risk of postnatal pathology,[2930] APD > 15 mm at any gestation represents severe hydronephrosis and requires close follow-up. [782223253133]…”
Section: Antenatal Evaluation and Monitoringmentioning
confidence: 99%
“…[432] Patients with persistence or worsening hydronephrosis in the third trimester show higher rates of postnatal pathology and require close follow-up. [45621233262] Sairam et al ., found that 88% cases with mild ANH resolved in utero or neonatal period, while one in three neonates with moderate to severe hydronephrosis persisting in the third trimester required postnatal surgery. [6] Hence, an ultrasound in the third trimester is valuable for identifying fetuses that require postnatal evaluation and follow-up.…”
Section: Antenatal Evaluation and Monitoringmentioning
confidence: 99%
See 1 more Smart Citation
“…Fetal hydronephrosis (HN) is the most common anomaly detected on antenatal ultrasonography, with an estimated prevalence of approximately 2–5.5% [ 1 3 ]. In most cases, HN is diagnosed in the absence of urinary tract obstruction, when the anteroposterior diameter of the renal pelvis is just above the normal range for gestational age [ 4 ].…”
Section: Introductionmentioning
confidence: 99%